Pengaruh Kepercayaan diri, Peran orang tua, Keterampilan terhadap Minat Berwirausaha - Adhis Darussalam Pamungkas; Ahmad Fahrudin; Arief Muda Kusuma; Sutina Sutina (Jurnal Ilmiah Wahana Pendidikan, 2022)
Entrepreneurship is one way to increase the opportunity for additional work. The business world is full of hope and a better future. Entrepreneurship can provide promising income. A large and unlimited income will be had for successful entrepreneurs. The important planting of entrepreneurship must be done from an early age and from school. The purpose of the study was to describe the effect of self-confidence, parental roles, and skills on interest in entrepreneurship. The study was conducted in 3 vocational schools in Bogor district. The number of respondents was 113 students. The method used is a quantitative method. The collected data is processed by testing assumptions (normality, homogeneity and linearity). Data was collected through a questionnaire. This study uses SPSS 23 to perform multiple regression tests, ANOVA. The results showed that there was an effect of self-confidence on interest in entrepreneurship, there was an effect of the role of parents on interest in entrepreneurship, there was an influence of skills on interest in entrepreneurship and there was an influence of self-confidence, the role of parents, and skills on interest in entrepreneurship together